Performance evaluation of the TE Air wireless handheld ultrasound in cardiac applications: a prospective comparative study - Ge, Beibei; Li, Mingxia; Cheng, Hanlin; Qi, Zhanru; Wang, Xiaoxian; Chen, Fen; Shi, Zhongqing; Guo, Guanjun; Shan, Chunjie; Qi, Jinyang; Luo, Shouhua; Xu, Fang; et al. (The Ultrasound Journal, 2025)
Aim: To evaluate the reliability and reproducibility of the TE Air wireless handheld ultrasound device in clinical cardiac imaging by comparing its performance with a high-end reference system. Methods: 161 patients for good-quality echocardiographic images were included in this prospective study. Each patient underwent sequential imaging using both the TE Air device (Mindray) and the high-end reference device (Philips EPIQ 7 C). Nine standard cardiac views were acquired. Image quality was assessed manually by two blinded echocardiographers and via proprietary AI software, respectively. The following key parameters were analyzed basing on the images: diastolic thickness of interventricular septal (IVSTd) and left ventricular posterior wall (LVPWTd), left ventricular end-diastolic (LVDd) and end-systolic diameter (LVDs), aortic diameter (AOD), left atrial anteroposterior diameter (LAD), Early (E) and late (A) diastolic velocities of the mitral valve in PW mode, as well as early diastolic velocities at the septal (EmS) and lateral (EmL) mitral annulus. Regional wall motion abnormality (RWMA), bicuspid aortic valve (BAV), atrial septal defect (ASD), left ventricular ejection fraction (LVEF) and valvular regurgitation degree were independently evaluated. Results: The TE Air demonstrated comparable image quality to the high-end reference system in both manual (64.95 ± 1.24 vs. 64.19 ± 1.63, P = 0.28) and AI-based evaluations (65.07 ± 1.02 vs. 63.80 ± 1.68, P = 0.06). Structural measurements showed high inter-device consistency, with ICCs of 0.77/0.74 for IVSTd/LVPWTd, 0.95/0.96 for LVDd/LVDs, and 0.82/0.98 for AOD/LAD (all P < 0.001). Functional parameters also demonstrated strong agreement (ICC: 0.91/0.92 for mitral E/A waves; 0.79/0.85 for EmS/EmL; P < 0.001). The TE Air had sensitivities of 81.8% for RWMA, 100% for ASD and BAV, and 93.5% for LVEF < 50%. Diagnostic agreement was excellent for LVEF (κ = 0.96, P < 0.001) and valvular regurgitation (weighted κ = 0.89, P < 0.001). Conclusion: The TE Air wireless handheld ultrasound device exhibits high agreement with high-end reference device in image quality, measurements, and clinical diagnoses, supporting its potential for widespread use in point-of-care ultrasound (POCUS) clinical applications.